Intravesical foreign object: A case report of autoerotism (Int J Surg Case Rep, 2020)
The lower urinary tract's foreign body is an uncommon condition, with the bladder being the most common site. Most foreign bodies are self-inserted via the urethra due to exotic impulses, psychometric problems, or sexual curiosity. We present a case of a 39 years old male with a lower urinary tract and abdominal pain. An abdominal CT Scan showed a sharp metal in the bladder. The patient underwent a successful extraction of a foreign body with biopsy forceps transurethrally. Foreign bodies in the bladder represent a urological challenge that requires prompt management. Treatment is determined by size, location, and shape. Minimally invasive procedures are recommended to prevent bladder and urethral injuries. However, surgical treatment should be performed if further injuries are expected. The suspected history and presenting symptoms are crucial and could lead to further investigations. Extraction should be carefully performed to minimize bladder and urethral injury. Gentle endoscopic management is the primary treatment with a high success rate. This case report aims to describe a case of the longest 12 cm sharp metal foreign material inserted to the bladder in South East Asia along with the management and subsequent condition to provide a better insight in managing future unusual cases.